Crustal Heterogeneity Onshore Central Spitsbergen: Insights From New Gravity and Vintage Geophysical Data - Senger, Kim; Ammerlaan, Fenna; Betlem, Peter; Brönner, Marco; Dumais, Marie Andrée; Gellein, Jomar; Henningsen, Tormod; Janocha, Julian; Johannessen, Erik P.; Liebsch, Jonas; Machleidt, Jakob; Mosočiová, Tereza; et al. (Geochemistry Geophysics Geosystems, 2025)
Gravity data provide constraints on lateral subsurface density variations and thus provide crucial insights into the geological evolution of the region. Previously, gravity data from the Norwegian Arctic archipelago of Svalbard comprised an onshore regional gravity database with coarse station spacing of 2–20 km, offshore gravity profiles acquired in some fjords, airborne gravity, and satellite altimetry. The sparse regional point-based onshore coverage hampered the direct integration of gravity data with seismic profiles acquired onshore Svalbard in the late 1980s and early 1990s. In April 2022, we acquired gravity data at 260 new stations along seven profiles from western to eastern Spitsbergen, with a cumulative length of 329 km. The profiles were acquired directly along selected seismic profiles and provide much closer station spacing (0.5–2 km) compared to the regional inland grid (2–20 km) acquired in the late 1980s (total number of onshore stations: 1,037). Having processed the data, we compared the first-order density trends of our new data with the legacy regional grid. The new gravity data are consistent with the regional data, imaging a gravity low in the western part of the area underlying a foreland basin and a gravity high in the northwestern part of the area likely associated with a basement high or denser basement. We compare the new and vintage gravity using maps and profiles, linked to the known major tectonic features such as major basinal axes and fault zones, as well as other geophysical data sets including seismics and magnetics.
CRIS-Team Scopus Importer:2025-01-31